From the Interruption to the Development of Language Awareness in Translation:Questioning Cognitive and Educational Issues - Büyükkantarcio lu, Nalan; Do an, Aymil (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper, emphasizing the importance of native language awareness in translation and drawing on problems observed in university students, sets out with an assumption that native language awareness, which is supposed to have satisfactorily developed either naturally or through previous stages of education, may undergo a serious process of “interruption” or “blockage ”, as we call it, during written translations made particularly from the source language (English) to the mother tongue (Turkish). The fact that stu¬dents can recognize their mother tongue mistakes either after self-monitoring or after the instructor’s remarks may indicate that translated texts, which are seemingly Turkish, yet lacking many of the naturally well-formed fea¬tures of the mother tongue discourse, suffer from such problems either due to the heavy concentration of mind on the source language structures or due to the problems originating from the gaps in the translation training. Performances of a total of 60 subjects, comprising an equal number of freshman and senior students from two different departments at Hacettepe University - Department of Linguistics and Department of Translation and Interpretation - have been compared through tests of English, mother tongue awareness and translation to find out (a) what actual reasons lie behind the problem, (b) whether there is any positive improvement from the freshman to the senior groups in both departments, and (c) whether extensive translation training marks a positive effect on students to help them avoid problems concerning native language awareness.